2018
DOI: 10.1063/1.5024798
|View full text |Cite
|
Sign up to set email alerts
|

Polarization nondegenerate fiber Fabry-Perot cavities with large tunable splittings

Abstract: We demonstrate a type of microcavity with large tunable splitting of polarization modes. This polarization nondegenerate cavity consists of two ellipsoidal concave mirrors with controllable eccentricity by CO2 laser machining on fiber end facets. The experiment shows that the cavities can combine the advantages of high finesse above 104 and large tunable polarization mode splitting to the GHz range. As the splitting of the cavity can be finely controlled to match atom hyperfine levels or optomechanics phonons,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…We showed that the effects of birefringence can become significant in the strong-coupling regime (C > 1) which has been recently demonstrated with both atoms [23] and ions [25] in open microscopic cavities. The ability to tailor non-negligible birefringence into these cavities has also recently been devel-oped [37,38]. Therefore, the experimental regimes discussed within this work are within current technological limits and have the potential to significantly impact present-day and future experiments.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…We showed that the effects of birefringence can become significant in the strong-coupling regime (C > 1) which has been recently demonstrated with both atoms [23] and ions [25] in open microscopic cavities. The ability to tailor non-negligible birefringence into these cavities has also recently been devel-oped [37,38]. Therefore, the experimental regimes discussed within this work are within current technological limits and have the potential to significantly impact present-day and future experiments.…”
Section: Discussionmentioning
confidence: 95%
“…To further examine birefringence-enhanced emission, figure 4a shows the extraction efficiency as a function of the cavity polarisation eigenmode splitting for decay rates ranging from {κ, γ} ≪ g to {κ, γ} ≈ g. It is striking that for a given set of {g, κ, γ}, increasing the cavity birefringence achieves enhanced photon extraction. Moreover, this is a practical consideration as birefringence can be tailored independently of other rates in the system via the ellipticity of the mirrors [19,37,38]. The improvement in photon extraction is most significant in the strong-coupling regime.…”
Section: B Birefringence-enhanced Photon Extractionmentioning
confidence: 99%
See 1 more Smart Citation
“…We thank K. Schüppert for contributions in the early stage of the experiment. While finalizing the manuscript, we become aware of a related method of producing asymmetric mirrors [35].…”
Section: Acknowledgmentsmentioning
confidence: 99%
“…Over the past few years, the main focus of research on CO 2 laser ablation of mirror templates on optical fibers has been developing multi-shot ablation procedures in order to achieve better control over the geometry of the concave shape [24][25][26][27]. These studies, alongside with improved analytical and numerical cavity models [28][29][30][31][32], notably contributed to recent breakthroughs in trapped ion CQED [33], trapped atom CQED [34], solid-state QED [35], and optomechanics [36].…”
Section: Introductionmentioning
confidence: 99%